Juvenile delinquency and juvenile violence in Jos, Nigeria - Smah, Sam O. (African Dynamics, 1997)
The central objective of this study is to provide researchers, government, interested individuals and organizations with a contemporary scenario of juvenile violence and general delinquency patterns in Jos. Its objectives are to determine the borderline between normal and delinquent life patterns of juveniles, to establish incidences, patterns and trends in juvenile violence and delinquency, to assess the extent of gender variables in juvenile violence and delinquency, to assess the impact of housing on juvenile delinquency, to establish the role of 'significant' others in juvenile violence and delinquency, to assess the consequences, policy implications and options for juvenile violence and delinquency control and management in Nigeria